SARS-CoV-2-specific T cell responses and immune regulation in infected pregnant women. (February 2022) - Hsieh, Li-En; Grifoni, Alba; Dave, Hiral; Wang, Jasmine; Johnson, Diana; Zellner, Jennifer; Sidney, John; Chambers, Christina; Franco, Alessandra
Highlights: The SARS-CoV-2-specific T cell response in pregnancy is well developed. Pre-existing inflammatory conditions do not affect the T cell response to SARS-CoV-2. The innate compartment relevant for the immune regulation is normal. Memory T cells were low close to delivery: tissue resident for neonatal protection? Abstract: We studied the T cell response to SARS-CoV-2 spike and non-spike peptide epitopes in eight convalescent pregnant women together with the immune monitoring that included innate tolerogenic dendritic cell populations important to maintain the immunological mother/fetus interface to address a potential risk for the antiviral cellular response in the outcome of pregnancy. Four subjects had pre-existing chronic inflammatory conditions that could have potentially affected the SARS-CoV-2-specific T cell response. Seven of eight subjects responded to SARS-CoV-2 peptides with differences within CD4+ T helper (Th) and CD8+ cytotoxic T cells (CTL). SARS-CoV-2-specific inducible regulatory T cells (iTreg) were numerous in circulation. CD4+ T cell memory included central memory T cells (TCM ) and effector memory (TEM ). As far as the CD8+ memory repertoire, TCM and TEM were very low or absent in eight of eight subjects and only effector cells that revert to CD45RA+, defined as TEMRA were measurable in circulation. T cells were in the normal range in all subjects regardless of pre-existing inflammatory conditions. The immune phenotype indicated the expansion and activation of tolerogenic myeloid dendritic cells including CD14+ cDC2 and CD4+ ILT-4+ tmDC. In summary, SARS-CoV-2 infection induced a physiological anti-viral T cell response in pregnant women that included SARS-CoV-2-specific iTreg with no negative effects on the tolerogenic innate dendritic cell repertoire relevant to the immune homeostasis of the maternal-fetal interface. All eight subjects studied delivered full-term, healthy infants.